Peran Pelayanan Kantor Pajak Pada Perilaku Kepatuhan Wajib Pajak - Mulyadi Mulyadi; Yofhi Septian Panglipurningrum; Andri Octaviani (Universitas Katolik Widya Karya Malang, 2023)
Taxes are an important source of state revenue, but there is a gap between the significant tax gap and the low tax ratio, indicating that tax effort in Indonesia is still low. Various breakthroughs made by the tax service office related to taxpayer compliance, such as conducting socialization, imposing sanctions and making information technology applications in tax administration activities continue to be carried out in order to improve and optimize services to taxpayers. The goal of this study was to find out how individual tax payer compliance is affected by the role that the Tax Service Office plays in the form of tax socialization and tax sanctions. Quantitative research is the method used. This research was carried out at KPP Pratama Surakarta. This study's primary data comes from questionnaires that were given to respondents who are registered as individual taxpayers at KPP Pratama Surakarta. The Likert scale is the one used to measure variables. The hypothesis is tested using multiple linear regression analysis in this study. The consequences of the review show that somewhat socialization of duties, execution of e-documenting, and burden sanctions significantly affect citizen consistence. Taxpayer compliance is positively and significantly impacted by the F test results of tax socialization, e-filing implementation, and tax sanctions simultaneously. The determination test (R2) yielded a result of 45.2%, and the remaining 54.8% was influenced by other variable factors that this study did not examine.